IMPLEMENTATION OF ZIDAM III LAND ASSET MANAGEMENT IN THE FRAMEWORK OF ADMINISTRATIVE, LEGAL, AND PHYSICAL ORDER USING GOOGLE EARTH: Implementasi Manajemen Aset Tanah Zidam III Dalam Rangka Tertib Administrasi, Hukum Dan Fisik Dengan Menggunakan Google Earth - Ferdinand Hasudungan Siagian; Samsul Bahari; Haris F (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Land asset management in Kodam III/Slw faces various challenges, including administrative, physical, and legal aspects. This has become quite a heavy task for Zidam III/Slw as the unit responsible for the management. Although there are efforts to optimally manage land assets, many problems still arise in the field, such as inaccuracies in administrative data, limited physical supervision, and legal issues related to land status. Therefore, more efficient solutions are needed to address these issues. This research aims to explore the use of information technology, specifically the Google Earth application, as a solution in land asset management at Kodam III/Slw. The research method used is qualitative with an exploratory approach and case study design, which allows the researcher to delve deeply into various aspects related to land asset management. The research results show that the Google Earth application has proven effective in strengthening administrative roles, facilitating physical supervision, and providing ease in land asset mapping. The use of this technology also provides benefits in improving coordination among the related parties. However, to address the existing legal issues, Zidam III/Slw needs to enhance advocacy channels in accordance with the applicable regulations. The implication of this research is the importance of adopting information technology in land asset management and the need for more intensive coordination between internal and external parties to support the resolution of the legal issues faced.